2016
DOI: 10.1155/2016/1532832
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TLR2, TLR4, and TLR9 in the Pathogenesis of Atherosclerosis

Abstract: Toll-like receptors (TLRs) are key players in the pathogenesis of inflammatory conditions including coronary arterial disease (CAD). They are expressed by a variety of immune cells where they recognize pathogen-associated molecular patterns (PAMPs). TLRs recruit adaptor molecules, including myeloid differentiation primary response protein (MYD88) and TIRF-related adaptor protein (TRAM), to mediate activation of MAPKs and NF-kappa B pathways. They are associated with the development of CAD through various mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 132 publications
3
121
0
Order By: Relevance
“…Specifically, an association has been reported between the Asp299Gly TLR4 gene polymorphism with acute coronary events in men but not in women . In addition, there is evidence showing that TLR4 is associated with the initiation, progression, and eventual rupture of the atheroma plaque . Although these studies have mainly looked at TLR4 in monocytes and T lymphocytes, evidence showing that PAMPs and DAMPs interact with platelet TLR4 and trigger platelet activation clearly indicates that increased expression and/or functionality of platelet TLR4 might be involved in the pathogenesis of atherosclerosis and acute coronary events.…”
Section: Relevance Of Platelet Tlr4 In the Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, an association has been reported between the Asp299Gly TLR4 gene polymorphism with acute coronary events in men but not in women . In addition, there is evidence showing that TLR4 is associated with the initiation, progression, and eventual rupture of the atheroma plaque . Although these studies have mainly looked at TLR4 in monocytes and T lymphocytes, evidence showing that PAMPs and DAMPs interact with platelet TLR4 and trigger platelet activation clearly indicates that increased expression and/or functionality of platelet TLR4 might be involved in the pathogenesis of atherosclerosis and acute coronary events.…”
Section: Relevance Of Platelet Tlr4 In the Clinicmentioning
confidence: 99%
“…48 In addition, there is evidence showing that TLR4 is associated with the initiation, progression, and eventual rupture of the atheroma plaque. 49 Although these studies have mainly looked at TLR4 in monocytes and T lymphocytes, evidence showing that PAMPs and DAMPs interact with platelet TLR4 and trigger platelet activation clearly indicates that increased expression and/or functionality of platelet TLR4 might be involved in the pathogenesis of atherosclerosis and acute coronary events. In this sense, it has recently been reported that patients with unstable angina pectoris have enhanced expression of both platelet TLR2 and TLR4 compared to patients with stable angina pectoris and subjects with normal coronary arteries.…”
Section: Relevance Of Platelet Tlr4 In the Clinicmentioning
confidence: 99%
“…Zhang Y et al found that DKK1 induced by ox‐LDL suppressed LOX‐1 expression via the Wnt canonical signaling pathway in macrophages. Roshan MH et al found that Wnt5a expression was decreased in atherosclerosis‐associated inflammation following TLR2 and TLR4 knockout, while He X et al showed that the TLR4 pathway up‐regulated Wnt5a in mesenchymal stem cells treated with LPS. Furthermore, He W et al found that Wnt5a also activated NF‐κB in LPS‐stimulated human dental pulp stem cells in a TLR4/MyD88 dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Among the TLRs mediating inflammation, TLR2, TLR4 and TLR9 are related to ischemic injury [16]. Previous studies have demonstrated the involvement of TLR2 and TLR4 in hepatic ischemia [1], but the role of TLR9 in liver ischemia is not clear yet.…”
Section: Discussionmentioning
confidence: 99%